DEVELOPMENT AND EVALUATION OF TRANSDERMAL PATCHES WITH CISSUS QUADRANGULARIS PLANT EXTRACT: Pharmaceutical Sciences-Pharmaceutics - DAS, RENUKA; KOLHE, SNEHAL; PATIL, ARUN; WADHER, KAMLESH; UMEKAR, MILIND (International Journal of Life Science and Pharma Research, 2018)
The aim of the present research work was to prepare and evaluate the transdermal patches of Cissus Quadrangularis extract. Cissus Quadrangularis Aquous extracts was prepared using Maceration method. The transdermal patch was prepared by the solvent evaporation method using hydroxy propyl methyl cellulose (HPMC E -15) in different concentrations Di butyl Phthalate and DMSO were used as plasticizers and permeation enhancer. The prepared transdermal patches were evaluated for their physiochemical characteristics such as physical appearance, weight uniformity, thickness, folding endurance; moisture content.